2008
DOI: 10.4319/lo.2008.53.6.2616
|View full text |Cite
|
Sign up to set email alerts
|

The role of organic acid exudates in liberating phosphorus from seagrass‐vegetated carbonate sediments

Abstract: Sediment-bound phosphorus (P) is a potential nutrient source for P-limited seagrasses inhabiting carbonate sediments. We explored the role of organic acid (OA) exudation by seagrasses in liberating mineral P from carbonate sediments. Organic acids can act to increase available P by dissolving carbonate sediment, competing with P for binding sites and complexing dissolution end products, and also by fueling microbial processes that change pore-water pH. We used dialysis tubing placed around individual roots in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 32 publications
3
34
1
Order By: Relevance
“…Increased sediment sulfide production releases P bound to oxidized iron (Heijs et al 2000) and P can then be taken up from pore water or the water column by the sea- ) between cages and control stations, at different sampling events grasses. Moreover, dissolution of carbonate sediments by organic acid exudates from seagrasses liberates P from the sediments (Long et al 2008). Therefore, the increased P availability in fish-farm sediments possibly induced uptake of P by seagrasses in excess of their metabolic demands, a process known as 'luxury consumption' (Romero et al 2006) which has been reported for seagrasses (Ferdie & Fourqurean 2004) and other primary producers (Romero et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Increased sediment sulfide production releases P bound to oxidized iron (Heijs et al 2000) and P can then be taken up from pore water or the water column by the sea- ) between cages and control stations, at different sampling events grasses. Moreover, dissolution of carbonate sediments by organic acid exudates from seagrasses liberates P from the sediments (Long et al 2008). Therefore, the increased P availability in fish-farm sediments possibly induced uptake of P by seagrasses in excess of their metabolic demands, a process known as 'luxury consumption' (Romero et al 2006) which has been reported for seagrasses (Ferdie & Fourqurean 2004) and other primary producers (Romero et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation may also enhance physical trapping of particulate materialthe importance of this process will depend on the tidal size and frequency, river input, rainfall, and geomorphology of a system (Sánchez-Corrillo et al, 2009). Organic acids released from vegetation (e.g., seagrass) may also increase available DIP by dissolving carbonate sediment, competing with P for binding sites, complexing dissolution end products, and by fueling microbial processes that change pore-water pH (Long et al, 2008). Aquatic macrophytes and seagrasses, for example, transport oxygen from their shoots to their roots and some of this oxygen will leak into the rhizo sphere, creating oxidized spots in an otherwise reducing environment (e.g., Koretsky et al, 2008).…”
Section: Exchange With Vegetated Systemsmentioning
confidence: 99%
“…The study site for this research was the shallow estuary of Florida Bay, Florida, USA during July and August of 2012. Three sites were chosen across a productivity and nutrient gradient, with the lowest amounts of seagrass biomass, sediment organic matter, and sedimentary total phosphorus present in the northeast and the highest amounts in the southwest [ Zieman , ; Fourqurean and Zieman , , Long et al ., ]. Each site was selected to have monotypic beds of the seagrass Thalassia testudinum at Duck Key (25° 10' 36.60" N, 80° 29' 20.52" W), Bob Allen Keys (25° 2' 9.27" N, 80° 41' 10.66" W), and Rabbit Key Basin (24° 58' 4.89" N, 80° 50' 19.80" W) (Figure ).…”
Section: Methodsmentioning
confidence: 99%